The Integration of Artificial Intelligence in Islamic Education through the Application of Augmented Reality in STEM Learning - Naya, Arsya; Fardyatullail, Haila; Sherin, Ayunda; Sefira, Reza (Universitas Muhammadiyah Surakarta, 2025)
Technology has a significant influence on various aspects of life, particularly in education. Artificial Intelligence (AI) emerges as a solution for Digital Learning 5.0 in enhancing innovation, systems, and learning effectiveness. However, this technology must be utilized appropriately through virtual media such as Augmented Reality (AR), which should be designed in innovative and creative ways. Through the integration of Islamic education and STEM learning, there is a strong commitment to apply AI in an adaptive and inclusive learning context supported by AR. The purpose of this study is to explain the role of AI in education, the opportunities and challenges of technology in Islamic education, and the impact of AR in STEM-based learning. This research employs a qualitative method using a comparative analysis approach through library research. The findings reveal that the integration of AI contributes to improving critical thinking skills, character development, and enriching the learning process effectively on a global scale. Nevertheless, this technology cannot stand alone; it requires harmony between science and divine revelation. AR serves as an educational solution that bridges digital and real-world learning experiences. STEM, as an integrative field of knowledge, plays a crucial role in fostering innovation, creativity, critical thinking, and learning effectiveness. Therefore, the integration of AI technology through AR can enhance critical intellectual capacity grounded in Islamic values.